2010
DOI: 10.1186/1471-230x-10-55
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell cycle-related proteins in gastric intramucosal differentiated-type cancers based on mucin phenotypes: a novel hypothesis of early gastric carcinogenesis based on mucin phenotype

Abstract: BackgroundAbnormalities of cell cycle regulators are common features in human cancers, and several of these factors are associated with the early development of gastric cancers. However, recent studies have shown that gastric cancer tumorigenesis was characterized by mucin expression. Thus, expression patterns of cell cycle-related proteins were investigated in the early phase of differentiated-type gastric cancers to ascertain any mechanistic relationships with mucin phenotypes.MethodsImmunostaining for Cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 34 publications
3
31
1
2
Order By: Relevance
“…Previous studies have shown that mucin expression in tumor cells plays a major role in gastric carcinogenesis [16,17]. In the present study, whereas the MSI-high phenotype (subgroup 1) was categorized by the expression of either mucin 5AC or mucin 6, phenotypic expression in subgroup 3 or subgroup 4 was closely associated with CD10 expression.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Previous studies have shown that mucin expression in tumor cells plays a major role in gastric carcinogenesis [16,17]. In the present study, whereas the MSI-high phenotype (subgroup 1) was categorized by the expression of either mucin 5AC or mucin 6, phenotypic expression in subgroup 3 or subgroup 4 was closely associated with CD10 expression.…”
Section: Discussionmentioning
confidence: 46%
“…intestinal-type adenocarcinoma is thought to be distinct from diffuse-type adenocarcinoma with respect to gastric carcinogenesis [16,24]. In the present study, intestinal-type IMNs, including differentiated-type GC, were the main target lesions used to identify molecular characteristics of early gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Cyclin D1 and E Increased cyclin T1 expression as a favorable prognostic factor in treating gastric adenocarcinoma are the key regulators of progression through the G1 phase of the cell cycle (13,14). Overexpression of cyclin D1 and E is considered an early biomarkers of gastric cancer (15).…”
Section: Introductionmentioning
confidence: 99%